Use of O-J-I-P Chlorophyll Fluorescence Transients to Probe Multiple Effects of UV-C Radiation on the Photosynthetic Apparatus of Euglena - Beneragama, Chalinda Koshitha; Balasooriya, B.L.H.N.; Perera, T.M.R.S. (International Journal of Applied Sciences and Biotechnology, 2014)
Although the kinetic chlorophyll fluorescence signals are rich in information, most of the chlorophyll fluorescence related studies deal only with the quantum yield of primary photochemistry (Fv/Fm). JIP-test based OJIP fluorescence transient analysis is relatively a new technique to investigate the environmental stress responses of photosynthetic organisms. In the present study, the deleterious effects of ultraviolet (UV) radiation on the photosynthetic machinery were probed by the JIP-test in Euglena, one of the most potent organisms for the future space stations. The cells were exposed to a series of UV-C doses and immediately after exposure, survival percentage was determined with Neutral Red staining, and the chlorophyll fluorescence was measured using AquaPen AP-C 100 fluorometer. Resultant OJIP transients were analyzed according to JIP-test, and several functional and structural parameters were derived to explain the PSII behavior. Results indicated that the UV-C induced inhibition of electron transport is severely affected due to higher sensitivity of dark reactions after QA -, represented as ψo, the electron transfer probability, than of the light dependent reactions, represented as φPo, the trapping probability. The performance index (PIABS) of PSII, which is a combination of the indices of three independent parameters, decreased markedly in exponential manner in response to UVC. Results illustrate the advantage of using a number of fluorescent parameters over the use of one parameter, often the Fv/Fm. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.10510 Int J Appl Sci Biotechnol, Vol. 2(4): 553-558